Thickness dependence of the superconducting properties of Y- Mo2N thin films on Si (001) grown by DC sputtering at room temperature - Haberkorn, N. (2018)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina